Kinetic coupling between electron and proton transfer in cytochrome c oxidase: simultaneous measurements of conductance and absorbance changes. - Adelroth, P (1996)
Bovine heart cytochrome c oxidase is an electron-current driven proton pump. To investigate the mechanism by which this pump operates it is important to study individual electron- and proton-transfer reactions in the enzyme, and key reactions in which they are kinetically and thermodynamically coupled. In this work, we have simultaneously measured absorbance changes associated with electron-transfer reactions and conductance changes associated with protonation reactions following pulsed illumination of the photolabile complex of partly reduced bovine cytochrome c oxidase and carbon monoxide. Following CO dissociation, several kinetic phases in the absorbance changes were observed with time constants ranging from approximately 3 microseconds to several milliseconds, reflecting internal electron-transfer reactions within the enzyme. The data show that the rate of one of these electron-transfer reactions, from cytochrome a3 to a on a millisecond time scale, is controlled by a proton-transfer reaction. These results are discussed in terms of a model in which cytochrome a3 interacts electrostatically with a protonatable group, L, in the vicinity of the binuclear center, in equilibrium with the bulk through a proton-conducting pathway, which determines the rate of proton transfer (and indirectly also of electron transfer). The interaction energy of cytochrome a3 with L was determined independently from the pH dependence of the extent of the millisecond-electron transfer and the number of protons released, as determined from the conductance measurements. The magnitude of the interaction energy, 70 meV (1 eV = 1.602 x 10(-19) J), is consistent with a distance of 5-10 A between cytochrome a3 and L. Based on the recently determined high-resolution x-ray structures of bovine and a bacterial cytochrome c oxidase, possible candidates for L and a physiological role for L are discussed.